2016
DOI: 10.1111/iju.13197
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein phosphatases in genitourinary cancers

Abstract: The prevalence of genitourinary cancers has been increasing rapidly worldwide over the past 10 years. Advances in diagnosis and treatment have improved the oncological outcomes of patients with genitourinary cancer. However, the precise mechanisms of cancer development are largely unknown. Among various biological mechanisms, reversible phosphorylation is crucial for regulating the activities of many proteins in cancer cells. In contrast to protein kinases, the roles of cellular protein phosphatases have not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…One possibility is the oncogenic activation of protein tyrosine kinases because of defective control molecules, such as protein phosphatases that are not able to properly control their substrate kinase activity. Protein phosphatases have been a key focus of PCa research as crucial regulators of AR and multiple kinase signaling pathways via phosphorylation and dephosphorylation‐dependent processes (45). Most importantly, phosphatase and tensin homolog (PTEN), a tumor suppressor and DUSP, has been extensively studied in human PCas (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the oncogenic activation of protein tyrosine kinases because of defective control molecules, such as protein phosphatases that are not able to properly control their substrate kinase activity. Protein phosphatases have been a key focus of PCa research as crucial regulators of AR and multiple kinase signaling pathways via phosphorylation and dephosphorylation‐dependent processes (45). Most importantly, phosphatase and tensin homolog (PTEN), a tumor suppressor and DUSP, has been extensively studied in human PCas (46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…One substance that plays a role in the negative regulation of tyrosine phosphorylation is protein tyrosine phosphatase (PTP). Although Igawa et al have reported that prostatic acid phosphatase is involved in the negative control of prostate cancer cell proliferation through regulation of PTKs, there are far fewer reports on PTPs in prostate cancer than there are on PTKs (31,32), hence, the details of the mechanism of action remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%